2017
DOI: 10.1089/vim.2017.0071
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Infection Outcome in HCV-Genotype 4

Abstract: Hepatitis C virus (HCV) infection represents a worldwide health problem and has been for long an attractive point of research due to diversity among different genotypes regarding unique geographical distribution and diverse treatment outcome. HCV is considered a major cause of chronic liver disease and cirrhosis, which leads to liver failure and hepatocellular carcinoma requiring liver transplantation. Of the HCV genotypes identified, HCV genotype 4 (HCV-4) is the least studied. HCV-4 is responsible for ∼10% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 97 publications
0
8
0
Order By: Relevance
“…Liver disease is a considerable cause of mortality and morbidity [5,28]. Accurate determination of the disease stage is mandatory for clinical decision-making.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Liver disease is a considerable cause of mortality and morbidity [5,28]. Accurate determination of the disease stage is mandatory for clinical decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…Liver brosis induced by Hepatitis C virus (HCV) is a dynamic, wound healing, process that results from ongoing damage to the hepatocytes from direct viral cytopathic effect or due to immunological response with subsequent activation of hepatic stellate cell and changes in extracellular matrix formation and degradation, including deposition of collagen [1]. In the era of treatment of chronic HCV using highly e cient direct-acting antivirals (DAAs), hepatic brosis staging as a triage for therapy indication is no longer as crucial as once believed [2][3][4][5][6]. Rather, precise identi cation of advanced hepatic brosis as well as cirrhosis is highly required for adjusting HCV therapy, tracking possible regression of liver brosis after achieving sustained virological response, and proper prevention and treatment of HCV-related end-stage liver disease complications [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the above and given the population of Egypt, which exceeds 95 million, we estimate that more than 6.5 million Egyptians are infected with the HCV virus, and most of those are caused by a genotype 4. Several genotypic studies have shown that genotype 4 of HCV accounts for 93.1% of HCV infections, and most (80.6%) of the Egyptians infected with HCV4 belong to subtype 4A[ 5 - 7 ]. It is likely that the subtype 4A was the main strain associated with antischistosomal therapy epidemic that occurred in the 1960s and 1970s and which was associated with the reuse of needles[ 8 , 9 ].…”
Section: Hepatitis C Virus In Egyptmentioning
confidence: 99%
“…In fact HCV4 is the predominant HCV genotype in the Middle East and North Africa, which accounts for 59% of HCV infections in Syria, 53% in Iraq, 54% in Kuwait, and 64% in Palestine. It is also reported to be a dominant genotype in Qatar, Saudi Arabia, and Libya[ 5 , 6 , 10 , 11 ] and is common in other parts of the Middle East such as Lebanon, Oman, and UAE. This may possibly be related to the migration of Egyptians, who represent a major workforce in some of these Middle Eastern countries, to these areas[ 5 , 11 ].…”
Section: Hepatitis C Virus In Egyptmentioning
confidence: 99%